Does second-line therapy affect the radiological progression of rheumatoid arthritis?. Issue 1 (February 1984) - Pullar, T; Hunter, J A; Capell, H A
Abstract : The effect of 'second-line' drugs on radiological progression in rheumatoid arthritis is not clear, and previous studies have yielded contradictory results. Sixty-seven patients with rheumatoid arthritis have been followed up clinically and radiologically for approximately 2 years (26 patients were receiving intramuscular gold, 21 penicillamine, 10 levamisole, and there were 10 controls who had consistently refused second-line therapy). Patients on gold and penicillamine showed improvement in erythrocyte sedimentation rate and haemoglobin over 2 years which was not seen in levamisole and control patients, but hand radiograph scores in all 4 groups showed statistically significant deterioration. There was a trend towards slowing of the rate of erosion in the gold and penicillamine groups in comparison with controls, but healing of erosions was extremely unusual.